Pemanfaatan Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam: Peluang dan Tantangan - YULITA PUTRI (CV. Eureka Artha Nusantara, 2026)
The development of Artificial Intelligence (AI) presents both opportunities and challenges for Islamic Religious Education (PAI). Its urgency lies in the need for learning that is relevant to the digital era without neglecting PAI's primary objective: the formation of noble character (akhlak mulia). This study aims to analyze the potential utilization of AI in PAI and identify the accompanying challenges. The research gap emerges from the scarcity of comprehensive studies highlighting AI integration in PAI from pedagogical, ethical, and value internalization perspectives. This research employs a qualitative library research method with content analysis of books, scientific articles, and official documents. The findings indicate that AI offers opportunities to enhance personalized learning, develop innovative media, expand access to learning resources, and improve teacher administrative efficiency. However, challenges include the accuracy of religious information, shifting teacher roles, academic ethics, digital literacy gaps, and the potential weakening of value internalization. Recommendations emphasize strengthening digital literacy, developing adaptive curricula, and implementing human-centered AI approaches to ensure technology utilization remains aligned with PAI's objectives of forming faithful, pious, and morally upright students.